Scribal Habits in the Slavonic Manuscripts with Athanasius’ Second Oration against the Arians - Lytvynenko, Viacheslav V. (Studia Ceranea, 2020)
This article introduces the readers to the scribal habits/practices in ten Slavonic manuscripts that contain Athanasius’ Second Oration against the Arians. These scribal habits are classified and analyzed according to eleven categories: (1) omissions, (2) additions, (3) substitutions, (4) transpositions, (5) non-sense readings, (6) marginal corrections, (7) marginal notes, (8) deletions, (9) erasures, (10) interlinear corrections, and (11) corrections within the text. The analysis of each manuscript is accompanied with the statistical tables that summarize the collected data according to these eleven categories, and there is a longer summary table in the Appendix. Of the ten manuscripts, two are analyzed in more detail as a way of illustrating how the Orations were copied and read in medieval times, and how theological concerns and local contexts affected the scribe’s interaction with the text.